Bacteriophage T4 Head Morphogenesis III. Some Novel Properties of Gene 13-Defective Heads - Hamilton, Daniel L. (1972)
The nature of phage precursors in gene 13-defective infected cells was studied by electron microscopy and pulse-chase isotopic labeling experiments. Our results suggest that both stable (20%) and fragile (70%) filled-head precursors accumulated in the absence of gene 13 product. Upon extraction, the fragile heads were found to lose most of their deoxyribonucleic acid and appeared unfilled with an average density of 1.34 g/cm(3) and a sedimentation coefficient of 300S. These unfilled heads differed from empty gene 13-defective heads which did not have any associated deoxyribonucleic acid and banded at an average density of 1.31 g/cm(3). Furthermore, it was found that a tsN38 (temperature-sensitive mutant in gene 13)- infected culture maintained at 41.5 C for increasing times led to a decrease in specific infectivity of 1,000S phagelike particles. Electron microscopy of these particles revealed that the decreased infectivity was due to an improper union of head and tails.